2019
DOI: 10.3389/fpls.2019.00249
|View full text |Cite
|
Sign up to set email alerts
|

The Specialized Roles in Carotenogenesis and Apocarotenogenesis of the Phytoene Synthase Gene Family in Saffron

Abstract: Crocus sativus stigmas are the main source of crocins, which are glucosylated apocarotenoids derived from zeaxanthin cleavage that give saffron its red color. Phytoene synthase (PSY) mediates the first committed step in carotenoid biosynthesis in plants. Four PSY genes encoding functional enzymes were isolated from saffron. All the proteins were localized in plastids, but the expression patterns of each gene, CsPSY1a , CsPSY1b , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…To produce transient transgenic plants in which green fluorescent protein (GFP)-tagged UGT709G1 was expressed under the con-troCheck supplier details setl of the 35S promoter, the GoldenBraid (GB) strategy was used as previously described (Ahrazem et al, 2019). The amplified fragment was introduced into the pUPD2 vector, and from this vector to pDGB3Ω1-GFP.…”
Section: Vector Construction For Subcellular Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…To produce transient transgenic plants in which green fluorescent protein (GFP)-tagged UGT709G1 was expressed under the con-troCheck supplier details setl of the 35S promoter, the GoldenBraid (GB) strategy was used as previously described (Ahrazem et al, 2019). The amplified fragment was introduced into the pUPD2 vector, and from this vector to pDGB3Ω1-GFP.…”
Section: Vector Construction For Subcellular Locationmentioning
confidence: 99%
“…The agroinfiltrated leaves were analyzed 3-5 d following infiltration, as previously described (Ahrazem et al, 2019). For GFP detection, the excitation source was an argon-ion laser at 488 nm, and emission was observed between 510 and 530 nm.…”
Section: Confocal Microscopy and Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoene synthases have directly evolved from bacteria to plants through various bacterial taxonomic groups and algae (Sandmann 2002 (Zhao et al 2011). A chaperone protein named Orange protein has been reported to help in the stability of phytoene synthases in many plants (Ahrazem et al 2019); no PSY stabilizing protein in bacteria has been reported so far.…”
Section: Number Of Amino Acids and Molecular Weightmentioning
confidence: 99%
“…The differences in localization, internal environmental conditions, the presence/absence of introns(Dibari et al 2012;Ahrazem et al 2019), and the presence/absence of signal peptides(Kadono et al 2015) might be the reason for the variation in sequence length among the different PSY proteins.The instability index of Meiothermus taiwanensis strain RP sequence is 31.09, which is well below the value of 40, above which proteins are deemed to be unstable. Thus, the RP PSY protein is stable in nature.…”
mentioning
confidence: 99%